Bostrichidae (Coleoptera) - Zahradník,Petr, (Life Sciences E-Book Collection, 2025., 2025)
The present World Catalogue of the family Bostrichidae (Coleoptera, Bostrichiformia) includes all taxa described up to 31 December 2023 and contains a complete list of subfamilies, tribes, genera, subgenera, species and subspecies, including synonyms. This book also contains detailed distributions for 98 genera and 599 species and subspecies for individual countries, broken down into zoogeographic regions. For selected "larger" countries (Russia, China, India, Australia, Canada, USA, Mexico, Brazil, Chile and Argentina), a finer division into subregions was used, which often followed the administrative divisions (states, districts, provinces) of these countries. The storage of the vast majority of the type material in public and private collections (if known) is indicated. All original descriptions of the taxa and several other publications dealing with the distribution of these species are listed in the bibliography. See Less